M-Kitchen’s tapai pulut and cookies workshop - Ismail, Ahsiah; Handayani, Dini Oktarina Dwi; Ahmad, Maznah; Mohamad Ali, Noor Azian; Mohamadali, Noor Azizah; Zulkifli, Izyani (KICT IIUM, 2023)
M-kitchen has organized a workshop to make Tapai Pulut and baking Cookies on the 17th of March 2023. The workshop has taken place at the CITA pantry, Kuliyyah of Information and Communication Technology (KICT), International Islamic University Malaysia (IIUM). The workshop was attended by Dr. Dini Oktarina Dwi Handayani, Dr. Maznah Ahmad, Dr. Ahsiah Ismail, Dr. Noor Azian, Dr. Izyani Zulkifli, Noor Azizah Mohamadali and the students from Usrah in Action subject.It was a full day workshop where two types of dishes, which are Tapai Pulut and cookies being taught to the participants. The Tapai Pulut Making was taught by Dr. Dini Oktarina Dwi Handayani and the cookies baking class was taught by Dr. Maznah Ahmad. The participants were looking forward to trying all the recipes taught by the instructors